« Vraies protectrices » et représentantes privilégiées des sans-voix : l’engagement des femmes dans la cause animale française à la fin du xixe siècle - Fabien Carrié (Genre & Histoire)
This article studies the mobilisation of women in the French animal protection movement at the end of the nineteenth century. It focuses specifically on the appropriation of the principles of antivivisectionism by French women activists and women of letters, which arrived from Britain at this time. It deploys a simultaneously internal and external analysis to study the trajectory of those conceptions within the society for the protection of animals and in the broader intellectual field. We aim to show how these women sought to assert “committed” definitions of the animal cause, in opposition to a scientifically defined orthodoxy which dominated the French animal protection movement at the time. This challenge to the dominant definition of the cause can also be conceived as a critique of the growing influence of doctors and scientists on women’s bodies and as an affirmation of renewed positions of critical women authors inside the intellectual field.